PENINGKATAN POPULASI ITIK LOKAL MELALUI PEMBERDAYAAN PETERNAK ITIK DI NAGARI SURIAN KECAMATAN PANTAI CERMIN KABUPATEN SOLOK - Linda Suhartati; Tertia Delia Nova; Qurrata Aini; Tevina Edwin (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
The laying duck farming business in Nagari Surian is generally managed traditionally. Ducks are released in the morning and return to the cage in the afternoon and there are farmers who keep their ducks moving according to the rice harvest time in the local area. Maintenance management that has not been managed properly and the lack of knowledge of farmers are the main obstacles faced at the activity location so that the productivity of ducks is still very low. This activity aims to identify these problems and find solutions by developing appropriate programs for the next three years. The method of activities carried out in this activity is through online and offline discussions and consultations. This program is implemented on a people's duck farm located in Nagari Surian, Pantai Cermin District, Solok Regency. Activities are carried out by discussing with duck farmers to find out the obstacles experienced and then developing programs to overcome these problems. From the program that has been prepared, it is hoped that the program can be implemented properly so that it can overcome the problems of breeders and can increase the local duck population and make Nagari Surian as one of the producers of duck eggs in West Sumatra Province.